ELECTRONIC INFORMATION AND TRANSACTIONS LAW AND BUSINESS DEVELOPMENT IN INDONESIA: CONFRONTATIONAL OR ACCOMMODATIVE? - Pakina, Ridho (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
Technological developments, including online transactions, can no longer be avoided. But unfortunately, in carrying out online transactions themselves, the consumer is often on the very weak side. Therefore, it is necessary to have a regulation for the implementation of online business in Indonesia. This study aims to see how the Information and Electronic Transaction Law (UU ITE) is present in business development in Indonesia, especially for consumers. This research will be carried out using a normative juridical approach. The data used in this research comes from various previous research results and several legal sources in Indonesia, especially the ITE Law. The results of this study then found that article 4 in the Consumer Protection Act (UUPK) explains various rights owned by consumers. Then specifically, the ITE Law explains how to protect consumers that occur in the realm of online transactions. The presence of the ITE Law, despite its controversy in Indonesian society, can save consumers from conducting online business in Indonesia.